A contribution to the identification of charcoal origin in Brazil II – Macroscopic characterization of cerrado species - Gonçalves, Thaís Alves Pereira; Nisgoski, Silvana; Oliveira, Julia S.; Marcati, Carmen R. [UNESP]; Ballarin, Adriano W. [UNESP]; Muñiz, Graciela I. B. (FapUNIFESP (SciELO), 2016)
The Brazilian Cerrado is the richest savanna in the world. It is also one of the biomes more threatened in the country and a hotspot for conservation priorities. The main causes of deforestation in Cerrado are agricultural practices, livestock and charcoal production. Although charcoal has a minor impact, its consumption represents the deforestation of 16.000 Km² of the Cerrado. To contribute for the biomes’s conservation it is very important to improve forestry supervision. Thus, in this work we present the macroscopic characterization of charcoal from 25 Cerrado’s species. We simulate the real conditions of forest controllers by using the magnifications of 10x, 25x and 65x. Likewise, the charcoals micrographs are all of transverse sections due to the larger amount of anatomical information. We also analyzed texture, brightness, vitrification, ruptures and some special features. The species present several differences in their anatomical structure. Although some of them are very unique, this work does not intent to identify charcoals only by macroscopic analyses. But it might give directions to future identification of genera or species. It also provides knowledge for government agents to verify the documents of forestry origin by fast analyzing a sample of charcoal itself.
Keywords: Charcoal anatomy; Forest control; Native species; Nature conservancy